2013
DOI: 10.1371/journal.pone.0063979
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D and Mild Hypocalcaemia Are Highly Prevalent among Young Vietnamese Children and Women and Related to Low Dietary Intake

Abstract: IntroductionIn many developing countries including Vietnam, data are lacking on vitamin D and calcium deficiencies whereas those deficiencies can play an important role in the development of bone health and possibly non-communicable diseases. The purpose of this study was to determine the overall prevalence of vitamin D and calcium deficiencies in women and young children and their nutritional related risk factors.MethodsA cross-sectional study conducted among 595 women of reproductive age and 532 children <5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 44 publications
5
23
1
Order By: Relevance
“…Only 17% of participants in our study had vitamin D levels <50 nmol/L, in contrast to a previous study from Vietnam where >50% children had insufficiency or deficiency . The relatively high vitamin D levels in our study may have reduced the effectiveness of vitamin D supplementation in preventing influenza.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…Only 17% of participants in our study had vitamin D levels <50 nmol/L, in contrast to a previous study from Vietnam where >50% children had insufficiency or deficiency . The relatively high vitamin D levels in our study may have reduced the effectiveness of vitamin D supplementation in preventing influenza.…”
Section: Discussioncontrasting
confidence: 91%
“…The attack rate for all respiratory viruses in our study was 35%, which is comparable to other studies that have used RT‐PCR to detect infection in children . A study in the same population in Vietnam reported similar attack rates as ours . Also, detection of the types of viruses and their relative frequency was similar to previous reports.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The knots were chosen according to conventional classification of iCa ranges: relative to the normal range of 1.15–1.25 mmol/L, we defined hypocalcemia as mild, moderate and severe as 0.9–1.15, 0.8–0.9 and <0.8 mmol/L, respectively. Hypercalcemia was divided into mild, moderate and severe as 1.25–1.35, 1.35–1.45 and >1.45 mmol/L, respectively [11], [12]. Potential multicollinearity between covariates in the model were quantified by using variance inflation factor (VIF) which provided an index that measures how much the variance of an estimated regression coefficient is increased because of collinearity [13].…”
Section: Methodsmentioning
confidence: 99%